Turbulent CO2 exchange and surface energy balance over melting fjord-ice in North-East Greenland - Wickström, Siiri (Helsingfors universitet, 2015)
This study aims to connect air-sea ice turbulent carbon dioxide (CO2) exchange and the surface energy balance over melting fjord ice. Recent studies have shown that sea ice melt might act as a significant CO2 sink in Arctic waters. Melt process have been suggested to dilute both brine and surface water partial pressures of carbon dioxide ( pCO2). Also biological activity and carbonate chemistry changes the air-ocean CO2 concentration gradient. Even small fluxes might be potentially significant as the maximum sea ice extent covers approximately 7 % of Earth's surface. As multi-year ice diminishes with the on-going climate change a bigger portion of the ice cover will experience melt in the summer season and thus the melt induced changes on the carbon cycling in the Arctic will have a greater effect. Surface energy balance consists of net radiation, turbulent fluxes of latent and sensible heat and conductive heat flux. During melt the sea ice surface transforms from a dry snow cover to melt ponds. Surface melt leads to a decrease in the surface albedo controlling the surface energy balance. Sea ice temperature affects both air-ice-ocean energy exchange and the permeability of the ice. My thesis is based on a 30 day measurement campaign in June 2014 from The Young Sound fjord, in North-East Greenland (74° 18' N, 20° 13' W). Turbulent fluxes of CO2 and H2O were measured with 10 Hz with two open-path infrared gas-analysers and two sonic anemometers at approximately 3 m height. One mast was used to measure basic meteorology (temperature, humidity, radiation, wind). Continuous measurements of surface water pCO2 were made 2.5 m below the ice. Conductive heat flux was determined from ice cores. The turbulent fluxes were calculated with the Eddy Covariance-methodology. Weak winds decreased the number of good quality measurements and created gaps in the time series. The measured CO2 flux ranged between 1.92 ja -3.2 µmol m-2 s-1 (positive fluxes being efflux) and sea ice was a net sink during the campaign. Sea ice ...